(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, accettato dal Direttore, riproduce il testo della Relazione tenuta presso l’Arcisodalizio della Curia Romana (Roma, Palazzo della Cancelleria, 16 gennaio 2014). SOMMARIO: Premessa - 1. Alle radici della duplice sovranità: il dualismo cristiano - 2. La questione della sovranità della Chiesa - 3. La sana cooperatio nell’Accordo di revisione concordataria - 4. Dialettica con gli Episcopati e Ecclesia Communio - 5.Sana cooperatio e res mixtae: in particolare 8 per mille e matrimonio - 6. Nuove sfide alla sovranità della Chiesa? Abstract In the article the Author takes stock of the situation regarding the sana cooperatio between State and Catholic Church 30 years after revision of the Italian Concordat. After dealing with the concept of Christian dualism and its historical development, the essay pays attention to the sovereignty of Catholic Church and highlights how in last years the CEI (Italian Conference of Catholic Bishops) - in conjunction with the Holy See - has taken on particular importance in the relationship between State and Catholic Church. Then there is a comparison between two issues which have had unexpected results: the Eight per thousand and the marriage. With regard to the Eight per thousand, in consideration of the economic crisis, the Author proposes that Catholic Church may accept a temporary reduction of the sums devolved to her or may use such sums in order to strengthen the projects in favor of the common good. With regard to the marriage, in consideration of the violation of religious marriage freedom, the Author hopes for a clarification by the State or, otherwise, the adoption of the personal statutes.